Β‐2‐himachalen‐6‐ol protects against skin cancer development in vitro and in vivo. (5th September 2017) - Daaboul, Hamid E.; Daher, Costantine F.; Taleb, Robin I.; Boulos, Joelle; Bodman‐Smith, Kikki; Boukamp, Petra; Shebaby, Wassim N.; Dagher, Carol; El‐Sibai, Mirvat; Mroueh, Mohamad A.
Abstract: Background: Previous studies in our laboratory showed that Daucus carota oil extract (DCOE) possesses remarkable in‐vitro anticancer activity and antitumour promoting effect against DMBA/TPA skin carcinogenesis in mice. Chemical analysis of DCOE led to the isolation of the β‐2‐himachalen‐6‐ol (HC), major sesquiterpene with a potent anticancer activity against various colon, breast, brain and skin cancer cells. This study investigated the anticancer activity of HC against invasive epidermal squamous cell carcinoma cells and evaluated its effect in a DMBA/TPA skin carcinogenesis Balb/c murine model. Methods: HaCaT‐ras II‐4 epidermal squamous cells were treated with HC (1, 5, 10, 25 and 50 μg/ml), and cell viability was evaluated with WST 1 assay kit. Cell cycle analysis was carried out by flow cytometry, and pro/anti‐apoptotic proteins were measured using Western blot. The effect of topical and intraperitoneal (IP) treatment with HC in mice was assessed using the DMBA/TPA skin carcinogenesis model. Cisplatin (2.5 mg/kg; IP) was used as a positive control. Papilloma incidence, yield and volume were monitored, and isolated papillomas were assessed for their pro/anti‐apoptotic proteins and morphology. Results: β‐2‐himachalen‐6‐ol showed a dose‐dependent decrease in cell survival with an IC50 and IC90 of 8 and 30 μg/ml, respectively. Flow cytometry analysis revealed that treatment with 10 μg/ml HC significantly increased the number of cells undergoing late apoptosis (28%), while 25 μg/ml caused a larger cell shift towards late apoptosis (46.6%) and necrosis (39%). A significant decrease in protein levels of p53 and Bcl‐2 and a significant increase in p21 and Bax were observed. Also, there was a significant decrease in p‐Erk and p‐Akt protein levels. The treatment of mice (IP and topical) with HC caused a significant decrease in papilloma yield, incidence and volume. Similar effects were observed with cisplatin treatment, but HC‐treated groups exhibited twofold to threefold increase in survival rates. Similar patterns in the pro‐ and anti‐apoptotic proteins were observed in mice treated with HC, except for a significant increase in p53 protein. Conclusions: In conclusion, HC treatment induced cell cycle arrest (low dose) and promoted apoptosis partly via inhibition of the MAPK/ERK and PI3K/AKT pathways with no significant toxicity to laboratory mice.